Exploring the photocatalytic potential of NbTiZrW-based high-entropy alloys with Hf/Mo/Ta additions: Influence of alloying elements on their structural and photocatalytic performance - Zakir, O.; Guler, O.; Idouhli, R.; Aklalouch, M.; Dikici, B.; Khadiri, M. E.; Simsek, T. (Elsevier Sci Ltd, 2026)
In this study, the photocatalytic performance of NbTiZrW-based high-entropy alloys (HEAs) with Hf, Mo, and Ta additions was investigated. The alloys were synthesized by mechanical alloying for 120 h under a high-purity Ar atmosphere to prevent oxidation. The photocatalytic activity of the samples was evaluated based on the degradation of methylene blue (MB) under UV irradiation. Structural and chemical characterizations were performed using energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The results showed that MB removal by adsorption reached 22.96 % for NbTiZrWHf, 21.90 % for NbTiZrWTa, and 47.01 % for NbTiZrWMo. The incorporation of Mo into the NbTiZrW alloy was found to enhance electrostatic interactions between MB molecules and the alloy surface. Upon UV irradiation, the degradation efficiency increased significantly, reaching 32.84 % for NbTiZrWHf, 82.02 % for NbTiZrWTa, and 46.13 % for NbTiZrWMo within 3 h. The improved performance of the NbTiZrWHf alloy was attributed to its low particle size, which provided a larger number of active sites for photocatalytic activity, as confirmed by SEM analysis.
Keywords: High entropy alloy; Photocatalyst; Adsorption; Methyl blue; Transition metal alloys